The Problem Based Learning Model in Learning to Excavate Information from Historical Texts In Class VI - Abdurohim, Agus; Hendriana, Heris; Mustika, Ika (JLER (Journal of Language Education Research), 2026)
The skill of extracting information from a text is part of reading comprehension. In this study, learning to extract information was carried out using a problem- based model. learning . So the purpose of this study is to determine the influence of the problem based model learning in learning to explore historical text information in class VI. The research method used is quantitative experiment, with sample population in control class ( VI.b ) and experimental class ( VI.a ). The results of the study showed that the average pretest in class VI.a was 67.83, while for class VI.b as the control class the average pretest was 67.42. The results of the posttest shows the average value of class VI.b (control class) is 77.98, while for class VI.a (experimental class) it is 80.93. The Sig . (2-tailed) value is 0.32, which means less than 0.05. So it can be interpreted that the experimental class (class VI.a ) has a higher change compared to the control class (class VI.b ). The conclusion of this study is the Problem Based model Learning can have a good influence on the skills of exploring historical text information in class VI of SD Negeri Harjasari 2.